Effect of the trimming of the toe region of healthy horses forelimb hooves on morphology, distal angles and locomotion by cinematography - Rosa, V. B.B. [UNESP]; Alonso, J. M. [UNESP]; Pizzigatti, D.; Charlier, M. G.S. [UNESP]; Watanabe, M. J. [UNESP]; Machado, V. M.V. [UNESP]; Hussni, C. A. [UNESP] (FapUNIFESP (SciELO), 2022)
Seven forelimb hooves from healthy horses were submitted to regular trimming and fourteen days later, submitted to toe trimming. Toe angle and length, lateral and medial heels, frog and sole length and width, distal, proximal, and metacarpal phalangeal interphalangeal angles were measured, as well as locomotion evaluation through cinematographic analysis. The measurements were performed ten, 14, 15, 30 and 45 days after the regular trimming, and at 14 days two measurements, one before and one after the toe trimming, were carried out. For cinematography, the sequence of supports and time spent in each support were taken. The comparison of the means obtained from the individuals regarding the variables, between limbs, limbs for each individual, time – points, moments for each individual and between limbs for each moment, as well as the time spent in each in the supports, was performed using ANOVA. Results lower than those of statistical significance (p<0.05) were submitted to Tukey’s test. The toe trimming promotes changes in toe length, angle, lateral heel angle, medial and lateral heel length, frog length, width, and sole length, and changes the pattern of the trot of horses.
[Efeito do casqueamento da região da pinça dos cascos torácicos de equinos sadios sobre a morfologia dos cascos, ângulos articulares distais e locomoção por cinematografia]
Keywords: Arthrogoniometry; Equine; Gait; Joint; Morphometry